Factors Associated with the Choice of Peritoneal Dialysis in Patients with End-Stage Renal Disease. (6th March 2016) - Chiang, Pei-Chun; Hou, Jia-Jeng; Jong, Ing-Ching; Hung, Peir-Haur; Hsiao, Chih-Yen; Ma, Tsung-Liang; Hsu, Yueh-Han
Abstract : Background . The purpose of this study was to analyze the factors associated with receiving peritoneal dialysis (PD) in patients with incident end-stage renal disease (ESRD) in a hospital in Southern Taiwan. Methods . The study included all consecutive patients with incident ESRD who participated in a multidisciplinary predialysis education (MPE) program and started their first dialysis therapy between January 1, 2008, and June 30, 2013, in the study hospital. We provided small group teaching sessions to advanced CKD patients and their family to enhance understanding of various dialysis modalities. Multivariate logistic regression models were used to analyze the association of patient characteristics with the chosen dialysis modality. Results . Of the 656 patients, 524 (80%) chose hemodialysis and 132 chose PD. Our data showed that young age, high education level, and high scores of activities of daily living (ADLs) were positively associated with PD treatment. Patients who received small group teaching sessions had higher percentages of PD treatment (30.5% versus 19.5%; P = 0.108 ) and preparedness for dialysis (61.1% versus 46.6%; P = 0.090 ). Conclusion . Young age, high education level, and high ADL score were positively associated with choosing PD. Early creation of vascular access may be a barrier for PD.